A REVIEW OF MUSLIM MARITIME TRADITION - Omar Bin Yaakob; Mohamad Pauzi Abdul Ghani; Faizul Amri Adnan (PERINTIS eJournal, 2021)
The ocean covers more than 75% of the earth surface. This vast expanse of water promises a wealth of opportunities as well as challenges. This paper describes a historical perspective of development of maritime ventures in the Islamic World from the time of the Prophet (pbuh) until the present day. The expansion of the Muslim caliphate entailed among others rapid growth in communication and transport system as well as the need for a well-organised naval fleet. The peak of Muslim naval power was during the rule of the Ottoman Empire when their warships held sway over the Mediterranean, the Red Sea and parts of the Indian Ocean. A survey of the present status of maritime military, commercial, education and R&D capacity in Muslim countries is presented and proposals put forward for improving collaboration in this field.